State-Owned Enterprises as Economic Drivers: Profitability and Solvency Analysis of Gross Domestic Product - Kartika Sukmaningtyas; Rousilita Suhendah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the effects of profitability and solvency on State-Owned Enterprises (SOEs) in Indonesia from 2012 to 2020. Methodology/approach: Data processing was carried out using dynamic panel data regression analysis with the Generalized Method of Moments (GMM) approach, assisted by Stata 18 software. Results: The results indicate that Net Profit Margin (NPM) has a positive and significant impact on economic growth, suggesting that operational efficiency within SOEs plays a role in driving national output. In contrast, Return on Equity (ROE) demonstrates a significant negative effect, which may reflect the inefficient reinvestment of profits or limited productive use of equity returns. Meanwhile, Return on Assets (ROA) and Debt Asset Ratio (DAR) show no statistically significant impact, implying that neither asset efficiency nor leverage structure alone strongly influences GDP growth during the observed period. Conclusions: The findings show that previous GDP growth positively influences current GDP, underscoring the need for SOE profit strategies to support long-term sustainable growth over short-term gains. Limitations: The financial indicators used in this study do not include other relevant dimensions, such as liquidity, which may influence national economic growth. Furthermore, this study does not explore the potential role of moderating or mediating variables (e.g., government spending or employment absorption) that could strengthen or weaken the relationship between SOEs’ financial performance and economic growth. Contributions: This study provides strategic implications for policymakers and SOE management to optimize financial performance to support long-term development goals, including the realization of the Indonesia Emas 2045 vision.